Differential α‐adrenergic modulation of rapid onset vasodilatation along resistance networks of skeletal muscle in old versus young mice - Sinkler, Shenghua Y. (J Physiol, 2016)
KEY POINTS: Rapid onset vasodilatation (ROV) initiates functional hyperaemia upon skeletal muscle contraction and is attenuated during ageing via α‐adrenoreceptor (αAR) stimulation, but it is unknown where this effect predominates in resistance networks. In gluteus maximus muscles of young (4 months) and old (24 months) male C57BL/6 mice, tetanic contraction while observing feed arteries and arterioles initiated ROV, which increased with contraction duration, peaked later in upstream versus downstream vessel branches and was attenuated throughout networks with advanced age. With no effect on muscle force production, inhibiting αARs improved ROV in old mice while activating αARs attenuated ROV in young mice. Modulating ROV through αARs was greater in upstream feed arteries and arterioles compared to downstream arterioles, with α(2)ARs more effective than α(1)ARs. ROV is coordinated along resistance networks and modulated differentially between young and old mice via αARs; with advanced age, attenuated dilatation of upstream branches will restrict muscle blood flow. ABSTRACT: Rapid onset vasodilatation (ROV) in skeletal muscle is attenuated during advanced age via α‐adrenoreceptor (αAR) activation, but it is unknown where such effects predominate in the resistance vasculature. Studying the gluteus maximus muscle (GM) of anaesthetized young (4 months) and old (24 months) male C57BL/6 mice, we tested the hypothesis that attenuation of ROV during advanced age is most effective in proximal branches of microvascular resistance networks. Diameters of a feed artery (FA) and first‐ (1A), second‐ (2A) and third‐ (3A) order arterioles were studied in response to single tetanic contractions (100 Hz, 100–1000 ms). ROV began within 1 s and peaked sooner in 2A and 3A (∼3 s) than in 1A or FA (∼4 s). Relative amplitudes of dilatation increased with contraction duration and with vessel branch order (FA<1A<2A<3A). In old mice, attenuation of ROV was greater in FA and 1A compared to 2A and 3A. With no effect on muscle force production, inhibiting αARs (phentolamine; 10(−6)  m) improved ROV in FA and 1A of old mice while subthreshold stimulation of αARs in young mice (noradrenaline; 10(−9)  m) depressed ROV most effectively in FA and 1A. In young mice, stimulating α(1)ARs (phenylephrine; 10(−7)  m) and α(2)ARs (UK 14304; 10(−7)  m) attenuated ROV primarily in FA. In old mice, inhibiting α(2)ARs (rauwolscine; 10(−7)  m) restored ROV more effectively in FA and 1A than did inhibiting α(1)ARs (prazosin; 10(−8)  m). We conclude that, with temporal and spatial coordination along resistance networks, attenuation of ROV with advanced age is most effective in proximal branches via constitutive activation of α(2)ARs.